Strengthening Pedagogical Competence Through Educational Hr Management: A Case Study At SMPN 1 Kotabaru - Edy Rakhmadi; Norliani; Muhammad Muhaimin; Aslamiah; Ahmad Suriansyah (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
The rapid digitalization of education has reshaped pedagogical practices, requiring teachers to continually strengthen their competence in designing, implementing, and evaluating technology-integrated instruction. This study investigates the educational Human Resource Management (HRM) strategies used to enhance teachers’ pedagogical competence in the digital era through a case study at SMPN 1 Kotabaru. Employing a qualitative approach with an exploratory case study design, data were collected from 12 informants, consisting of school leaders, HR development coordinators, and teachers. The data collection techniques included semi-structured interviews, participant observation, and document analysis. Data were analyzed using Miles and Huberman’s interactive model, encompassing data reduction, data display, and conclusion drawing. The findings reveal that HRM strategies are operationalized through four core components: systematic competency needs mapping, practice-based modular training, continuous performance monitoring, and reflective post-training evaluation. Teachers perceive these strategies as supportive, particularly when training emphasizes applicability, collaboration, and contextual problem-solving. Institutional challenges include limited time allocation, resistance to technological changes, and inconsistent training continuity. Five success-inducing factors are identified: visionary leadership, collaborative school culture, reflective evaluation mechanisms, institutional policy support, and teachers’ technological readiness. Theoretically, this study contributes to the discourse on strategic HRM in digital-era education, while practically offering guidance for policymakers and school leaders in designing adaptive and sustainable teacher development systems